Social perception of the integration of Romani people (Gypsies) into the labor market - Rus Mihaela,; Sandu Mihaela Luminita,; Rus, Ciprian Vasile (Technium Social Sciences Journal, 2021)
Over the years, the gypsies have been the subject of various discussions, being cataloged as "dirty gypsies, thieves, lazy and who do not want to learn" and especially those responsible for the negative image of Romania abroad, in other words they were "the apple of discord" in the Romanian society. The "valves" were also opened after the incidents in France 2010 that generated new discussions on the problems due to the Roma, the optimal solution in solving these problems being the integration of the Roma in the society. However, the vast majority of Romanians are reluctant to integrate the gypsies into society, especially on the labor market, and this is due to the public image, most often negative, which gypsies "enjoy". We chose this theme, in the idea of supporting the integration of the Roma in the labor market, considering this step an advantage in favor of the economy of the country, since the limited access of Roma people to the labor market causes Romania to lose at least 887 million euros annually, according to a report by the World Bank. Also, we consider it is necessary to integrate them in the labor market and due to the fact that the taxes and social contributions that they pay are far below the majority population, with notable effects on the Gross Domestic Product. A final argument that contributed to the choice of this theme is that the integration of the members of this population in the labor market could be a positive proof for the efficiency of the policies and projects implemented over time in their favor.